2015
DOI: 10.2480/agrmet.d-14-00029
|View full text |Cite
|
Sign up to set email alerts
|

Growth of Japanese and hybrid larch seedlings grown under free-air O<sub>3</sub> fumigation—an initial assessment of the effects of adequate and excessive nitrogen

Abstract: Ground-surface ozone (O 3 ) and nitrogen (N) deposition in forests are increasing rapidly in East Asia. The Japanese larch (JL) has been transplanted from central Japan to northern areas. Because the JL suffers from shoot blight disease and grazing by voles, the hybrid larch (F 1 ) was developed to overcome these weak points. For sustainable use of these larches, we should know the growth responses of larches to elevated O 3 (eO 3 ) and excessive N deposition in northern Japan. Two-year-old JL and F 1 seedling… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
1
1

Relationship

3
5

Authors

Journals

citations
Cited by 25 publications
(14 citation statements)
references
References 24 publications
1
11
0
Order By: Relevance
“…However, high litter N concentration was observed at only N100P0 in both 2015 and 2016. Previous reports indicated that excessive N loading leads to high litter N concentration (Aber et al 1989, Uddling et al 2006, Watanabe et al 2011, Dong-Gyu et al 2015. The characteristic of N100P0 is that it is P limited and has a high needle N: P ratio.…”
Section: Abovegroundmentioning
confidence: 99%
“…However, high litter N concentration was observed at only N100P0 in both 2015 and 2016. Previous reports indicated that excessive N loading leads to high litter N concentration (Aber et al 1989, Uddling et al 2006, Watanabe et al 2011, Dong-Gyu et al 2015. The characteristic of N100P0 is that it is P limited and has a high needle N: P ratio.…”
Section: Abovegroundmentioning
confidence: 99%
“…Ozone (O3) sensitivity of larch seedlings is strongly related to the nitrogen condition of the soil (e.g. [21,24]) as well as the stomatal conductance (Gs) [6]. O3 sensitivity appears to increase with the foliar N content in many plant species, since both Psat and Gs increase (e. g. [4,6]).…”
Section: 1differences In Photosynthetic Characteristics Between Shmentioning
confidence: 99%
“…Sensitivity to O3 in larch depends strongly on N conditions [20,21] as well as Gs (i.e. gas diffusion in both water and CO2, e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Details of the O3 exposure in field station as well as the plot design can be found in Watanabe et al (2013). O3 concentration of 80 ± 7 nmol mol -1 was applied during daylight hours (about 7 h per day) from early-August to mid-November in treatment plots, while at the same time, the control plots were subjected to ambient daytime O3 concentration of 26.5 nmol mol -1 (Kam et al 2015) Each of the free-air enrichment plot was unevenly divided into 3 parts, replaced with 3 different soil types: about 84% of the plot area was divided into 2 parts, each equally consisting of brown forest soil (B) and volcanic ash soil (V); about 16% of the area was serpentine soil (S). All of these soil types are widely distributed across northern Japan (Kim et al 2011).…”
Section: Experimental Site Descriptionmentioning
confidence: 99%
“…Furthermore, elevation of O3 is expected to continuously increase for at least several decades in the foreseeable future (Ohara et al 2007). In addition, eO3 can accelerate foliar senescence (Hoshika et al 2012) and reduce the retranslocation rate of nitrogen (N - Kam et al 2015), resulting in nutrient deficiencies in leaves caused by the decline of N acquisition (Karnosky et al 2007).…”
Section: Introductionmentioning
confidence: 99%